(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In the article information on the granulometric composition of the soils of Konimex natural geographical region is presented. On the basis of scientific research, the author proved that layers of light and medium mechanical composition are mainly formed in sandy desert soils > irrigated gray-brown > irrigated brown-meadow > irrigated meadow soils. The main factor in this was the periodicity of irrigation, and finally, the process of disaggregation in the structure of the soil occurred.